2017
DOI: 10.1111/evj.12720
|View full text |Cite
|
Sign up to set email alerts
|

Fracture of the medial intercondylar eminence of the tibia in horses treated by arthroscopic fragment removal (21 horses)

Abstract: SummaryBackgroundFractures of the medial intercondylar eminence of the tibia (MICET) are scarcely reported in horses.ObjectivesTo report the clinical and diagnostic findings, surgical treatment and outcome in a series of horses presented with MICET fracture and treated with arthroscopic fragment removal.Study designMulticentre retrospective case series.MethodsCase records of horses diagnosed with MICET fractures that had undergone surgical treatment were reviewed. Follow‐up information was obtained from re‐exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In another study, fractures of the medial intercondylar eminence of the tibia were also considered to most likely relate to a traumatic event; and lateral motion of the medial condyle was the proposed cause for the fracture. The potential pathogenesis involving avulsion fracture of the cranial cruciate ligament insertion was excluded as the ligament was intact or only mildly damaged in most cases . In contrast, the most common stress‐related fractures in Thoroughbred racehorses were located in the humerus, tibia and ilium .…”
Section: Fracture Prevalence and Pathogenesismentioning
confidence: 99%
“…In another study, fractures of the medial intercondylar eminence of the tibia were also considered to most likely relate to a traumatic event; and lateral motion of the medial condyle was the proposed cause for the fracture. The potential pathogenesis involving avulsion fracture of the cranial cruciate ligament insertion was excluded as the ligament was intact or only mildly damaged in most cases . In contrast, the most common stress‐related fractures in Thoroughbred racehorses were located in the humerus, tibia and ilium .…”
Section: Fracture Prevalence and Pathogenesismentioning
confidence: 99%
“…In orthopaedics, this is frequently done through retrospective case series, which are often multi-centred in nature to obtain sufficient case numbers. An example of this is the description of fractures of the medial intercondylar eminence of the tibia, and documentation of the treatment of this fracture by arthroscopic surgery [3]. In the series of 21 cases, which were treated by arthroscopic removal of the fracture fragment, it was found that the injury was commonly associated with a traumatic event.…”
mentioning
confidence: 99%